(untitled) - Tawney, R. H. (Gloucester, Mass., 1962)
In one of the true classics of twentieth-century political economy, R. H. Tawney investigates the way religion has moulded social and economic practice. He tracks the influence of religious thought on capitalist economy and ideology since the Middle Ages, shedding light on the question of why Christianity continues to exert a unique role in the marketplace. The book offers an incisive analysis of the morals and mores of contemporary Western culture.
Keywords: Cơ Đóc giáo,Christianity; Khía cạnh kinh tế,Lịch sử,Economic aspects,History